The relationship between the ratio of omega-6 and omega-3 consumption with caesarean section - Mustikaningrum, Fitriana; Rahmaningtyas, Anindya; Ningtyas, Puput F.E.; Mardiyati, Nur Lathifah; Binti Che Ku Jusoh, Tengku Farizan Izzi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background : Many of research explained that Omega-3 and Omega-6 consumption during pregnancy affect delivery method. Omega-3 and omega-5 affect uterus contraction. The prevalence of caesarean section in 154 countries were 21.1%, and 43% in Primary health care. Caesarean section has a risk to get complication during and after parturition also could increase maternity cost. Objectives:  The aim of study was to determine the relationship between ratio omega-6: omega-3 intake and the incidence of cesarean section in postpartum mothers in the Bendosari Primary Health Care area. Method: This was observational study with cross sectional approach. The subjects of the study were 66 postpartum mothers who met the inclusion and exclusion criteria and were selected using the purposive sampling method. Data of omega-3 and omega-6 intake during the 2-3rd semester tri pregnancy period were obtained by interview method using the Semi Quantitative Food Frequency (SQ_FFQ) form. The relationship between omega-3 intake and caesarean section was analyzed with the Chi-Square test (P<0,05), while Fisher’s exact test was used to analyzed the relationship between intake ratio of omega-6 and omega-3 (P<0,05). Result: There was a relationship between omega-3 intake and ratio between omega-6: omega-3 intake with caesarean section with P-value 0.03. The mother who consume high omega-3 had prevalence ratio 3,6 times higher to have normal delivery compared than mother who had low consumption of omega-3. Moreover, mother who had sufficient ratio of omega 6: omega 3 in their diet had prevalence ratio 9 times higher to have normal delivery compared with mother who had high ratio of omega 6: omega 3in the diet during pregnancy. Pregnant women suggests to consume high omega-3 and sufficient ratio omega-6:omega-3 to prevent risk of  caesarean section